Penerapan Manajemen Bandwidth Menggunakan Metode Hierarchical Token Bucket (HTB) - Tukino Tukino; Algifari Maulana (LPPM Universitas Putera Batam, 2022)
Technology and communication are increasing rapidly and in accordance with the development of modern society which is very much looking for easy services and looking for in all fields, so that the need for information and communication is increasing greatly. Year after year, many providers enter residential areas to provide internet services by purchasing cheap packages with available bandwidth, it is possible for settlements to have no service from bandwidth vendor providers because they have not fulfilled such as the existence of a tower for network delivery. Because of that the need for a method in bandwidth management. In modern times like this, the need for the internet is increasing sharply, both for working with data processing and entertainment. In this network analysis there is a problem, after grouping data from customers where there are complaints about the bandwidth obtained does not match the selected package, so it causes user discomfort. To overcome this problem we found a solution by applying the Hierarchical Token Bucket method. From the application of the Hierarchical Token Bucket method, it can be concluded that the bandwidth obtained between users becomes more stable and even, this can be proven through Speedtest and traffic monitoring.